Industrial innovation in China : the factors determining success or failure - Fu, Zhenyu (New York : Routledge, 2021)
"This book, based on extensive original research, examines the factors which lead to successful innovation in Chinese industry. Considering in detail the large and important Chinese mining industry, it argues that innovation is key for success in all industries, not just new "tech" industries. It reveals how the interaction of universities, governments and industries is highly significant, considers how some parts of the industry, such as the mining and mineral processing stages, are more innovative than other stages, such as prospecting and manufacturing, and suggests that this is explained both by the distance between final products and the market and commercialisation and by the intensity of the interaction between the industrial company and the university or research institute. Throughout, the book includes examples and case studies to highlight the points made"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Industries -- China -- Technological innovations; Industrial policy -- China; Success in business -- China